2012
DOI: 10.3831/kpi.2012.15.002
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3-independent Down-regulation of GABABR1 due to Treatment with Korean Herbal Extract HAD-B Reduces Proliferation of Human Colon Cancer Cells

Abstract: Objectives:Many efforts have shown multi-oncologic roles of galectin-3 for cell proliferation, angiogenesis, and apoptosis. However, the mechanisms by which galectin-3 is involved in cell proliferation are not yet fully understood, especially in human colon cancer cells.Methods:To cluster genes showing positively or negatively correlated expression with galectin-3, we employed human colon cancer cell lines, SNU-61, SNU-81, SNU-769B, SNU-C4 and SNU-C5 in high-throughput gene expression profiling. Gene and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
5
0
1
Order By: Relevance
“…Several studies supported the anticancer effect of HAD-B in various cancer cells including human NSCLC cells. 15 - 19 HAD-B1, a herbal aqueous extract, composed of 4 critical herbs (Panax Notoginseng Radix, Cordyceps militaris, Panax ginseng CA Mey, and Boswellia carteri Birdw), was developed to focus on lung cancer treatment. This study was conducted to investigate the anticancer effects of the HAD-B1 combined with afatinib on H1975 EGFR-L858R/T790M double mutation lung cancer cells with the biological mechanism and solid tumor growth in nude mice bearing a H1975 human lung cancer xenograft.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies supported the anticancer effect of HAD-B in various cancer cells including human NSCLC cells. 15 - 19 HAD-B1, a herbal aqueous extract, composed of 4 critical herbs (Panax Notoginseng Radix, Cordyceps militaris, Panax ginseng CA Mey, and Boswellia carteri Birdw), was developed to focus on lung cancer treatment. This study was conducted to investigate the anticancer effects of the HAD-B1 combined with afatinib on H1975 EGFR-L858R/T790M double mutation lung cancer cells with the biological mechanism and solid tumor growth in nude mice bearing a H1975 human lung cancer xenograft.…”
Section: Introductionmentioning
confidence: 99%
“…Pinto et al [28] indicated that there is a complicated cell communication in response to ionizing radiation revealed by primary human macrophage-cancer cell culture. Kim et al [29] reported that IFITM1 expression was positively correlated with galectin-3 via receptor signaling protein activity in human colon cancer cells. The cell junctions might lead to cancer due to the differences in cell junctions for colorectal cancer [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, antitumor effects of HAD-B were investigated in several in vitro models ( 7 10 ). However, to the best of our knowledge, there is no preceding report on the in vivo antitumor effect of HAD-B.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the anti-angiogenic and anti-metastatic effects of HAD-B ( 7 , 8 ). In addition, the suppression of γ-aminobutyric acid B receptor 1 (GABABR1) and heat shock protein 27 (HSP27) expression was demonstrated as a molecular mechanism underlying the anti-cancer effect of HAD-B ( 9 , 10 ). However, previous studies have not provided evidence on the immunomodulatory action of HAD-B.…”
Section: Introductionmentioning
confidence: 99%